Inscrire son pouvoir dans l'espace urbain : multiplicité des autorités locales et compétition urbanistique à Toulouse dans le dernier siècle de l'Ancien Régime - Nicolas Marqué (Les Cahiers de Framespa)
The city of Toulouse changed during the last century of the Old Regime, not really because of its population growth but because of political decisions. There were many local authorities in town which all wished to use urban planning to show their power to the community of the inhabitants. On the one hand, these rivalries may have fueled the transformations of the town, since each power wished to transform the urban space, but, on the other hand, this competition was also a threat to urban planning because almost each power wished to fight against its competitors' projects.